Role of Small States in International Relations Comparative Analysis of the Czech Republic and Israel - Hlavsová, Aneta, 1989- (2015)
This study is titled Role of Small States in International Relations: Comparative Analysis of the Czech Republic and Israel and its main purpose is to analyze a typical small state's behavior in the international arena on the examples of the Czech and Israeli foreign policy. It is divided into four respective sections -- a theoretical framework, historical background, and the two case studies, and it strives to answer a foundational question whether the Czech Republic and Israel can be considered small players in international relations based on the theoretical definition of the notion of a small state as well as the countries' current foreign policy approaches and tools.